Diseño de una planta de deshidratación y secado de lodos industriales provenientes del proceso de enfriamiento de un horno incinerador de la Empresa Prosarc S.A ESP. (2022)
Nowadays there is a need to minimize waste, as well as to give them a correct and safe disposal, being these two aspects quite relevant worldwide, which leads to the search for technological alternatives and changes in management policies that allow the generation of non-hazardous and more stable waste for its correct disposal or reuse. During the development of this research project, sludge treatment was particularly studied for the company PROSARC S.A., which treats chemical, biological and industrial wastes; with the purpose of implementing a plant or equipment that would allow the dehydration and drying of this sludge, with the objective of reducing the environmental impact and the operational expenses currently generated by a third party, which is reflected in the annual balance sheet submitted by the company. In the first instance, a bibliographic review was carried out, where different important concepts that complement this research and introduce the reader to the subject to be dealt with are addressed; this first phase is important since it will allow the reader to understand in a simpler way what is described later on.